THE INFLUENCE OF 3D POP-UP STORYBOOK IN THE OHIS, DMFT, DMFT, DENTAL HEALTH KNOWLEDGE & BEHAVIOR OF GRADE 1 STUDENT AT SDN BAKALANKRAJAN 2 - Widodorini, Trining; Istikharoh, Feni; Wardhani, Nabilah Kusuma; Musfira, Naadhira; Rubiyanti, Safira Yusinta (Caring: Jurnal Pengabdian Masyarakat, 2023)
Background: Caries is one of the serious health problems, especially in elementary school students. According to Riskesdas in 2018, Indonesian children aged 5-6 years categorized in severe early childhood caries. After the covid cases have decreased in Indonesia , health promotion was held again in the school. Storybook is one of the media that can be used for health promotion in children, with attractive storyline and pictures as well. Purpose: To identify the influence of “Si Gilang dan Ramuan Ajaib'' 3D Pop-Up storybook in the OHI-S, DMFT, dmft index, dental health knowledge and behavior of grade 1 students at SDN Bakalankrajan 2. Methods: This was a numerical comparative study with a cross-sectional approach. The population were grade 1 elementary school students in SDN Bakalankrajan 2 in Malang. Results: After 3D Pop-Up storybook intervention twice time and after 30 days follow-up, there is a change in the OHIS, DMFT, dmft, knowledge and tooth brushing behavior compare to the score before intervention. The OHIS index has increased (p=0,000), DMFT index has decreased (p=0,974), the dmft index have increase quite high (p=0,106), knowledge level and tooth brushing behavior has increased on average quite well (p=0,024). Conclusion: Education intervention using a 3D pop-up children's storybook entitled